Identifying legitimate websites selling medicines in South Africa - Divishka Balraj; Nomvelo Mntambo; Kuyabonelelwa M. Lembede; Menelisi Madikane; Della-Reece Daniel; Deanne Johnston (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: The online sale of medicines has skyrocketed globally, where medicines are purchased in the comfort and privacy of one’s own home. However, there are an increasing number of illegal websites selling counterfeit and falsified medicines.